Association between Chinese visceral adiposity index and risk of new-onset hypertension in middle-aged and older adults with prediabetes: evidence from a large national cohort study - Lanlan Li; Lanlan Li; Linqiang Xi; Qianhui Wang (Frontiers in Public Health)
PurposeChinese Visceral Adiposity Index (CVAI) has been found significantly associated with hypertension in general and type-2 diabetes adults. However, the predictive value of CVAI for the incidence of hypertension in adults with prediabetes is unclear. This study aimed to assess the predictive utility of the CVAI for the new onset of hypertension in middle-aged and older adult Chinese individuals with prediabetes.MethodsA prospective cohort study was conducted involving participants aged 45 years and above with prediabetes from the 2011–2012 cohort of the China Health and Retirement Longitudinal Study (CHARLS). Logistic regression models were utilized to investigate the association between CVAI levels and the risk of new-onset hypertension.ResultsThe study included 2,186 participants, among whom 444 (20.31%) developed hypertension. Significantly higher incidence rates of hypertension were observed in individuals belonging to the highest quartile group (Q4) compared to those in the lowest quartile group (Q1) of CVAI (29.41% vs. 14.69%, p < 0.001). Multivariate logistic regression analysis indicated that participants in Q4 had a 1.91-fold greater risk of hypertension development compared to those in Q1 (odds ratio (OR): 1.91, 95% confidence interval (CI): 1.49–2.45, p < 0.001). The area under the receiver operating characteristic (ROC) curve (AUC) demonstrated that CVAI exhibited superior performance in discriminating individuals at heightened risk of hypertension compared to other obesity-related indices (p < 0.001). A subgroup analysis revealed that age may modulate the relationship between CVAI and new-onset hypertension, with a more pronounced interaction observed among participants below 60 years of age (P for interaction: 0.026).ConclusionElevated CVAI levels were significantly associated with an increased risk of developing hypertension. CVAI proves to be a reliable and effective tool for risk stratification in middle-aged and older adult Chinese individuals with prediabetes, underscoring its substantial implications for primary prevention of hypertension and public health strategies.